2014
DOI: 10.1210/jc.2013-2924
|View full text |Cite
|
Sign up to set email alerts
|

Increased Scalp Hair Cortisol Concentrations in Obese Children

Abstract: Hair cortisol concentration, a measure for long-term cortisol exposure, was higher in obese children than normal-weight children. This suggests long-term activation of the hypothalamus-pituitary-adrenal axis in obese children and may provide a novel target for treatment of obesity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
83
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 32 publications
15
83
3
2
Order By: Relevance
“…The association between cortisol and adiposity has been debated for a long time, with most studies showing a relative increase in urinary cortisol, but a decrease or unaffected cortisol in time-point measures (blood or saliva) [25]. However, we and others have reported increased HCC in association with increased BMI and abdominal adiposity [14][15][16][26][27][28], supporting the hypothesis that a slight increase in long-term cortisol exposure is associated with increased adiposity. Our results indicate that also in patients with structural heart disease long-term cortisol is associated with increased BMI, and could therefore modulate CVD risk.…”
Section: Discussionsupporting
confidence: 56%
“…The association between cortisol and adiposity has been debated for a long time, with most studies showing a relative increase in urinary cortisol, but a decrease or unaffected cortisol in time-point measures (blood or saliva) [25]. However, we and others have reported increased HCC in association with increased BMI and abdominal adiposity [14][15][16][26][27][28], supporting the hypothesis that a slight increase in long-term cortisol exposure is associated with increased adiposity. Our results indicate that also in patients with structural heart disease long-term cortisol is associated with increased BMI, and could therefore modulate CVD risk.…”
Section: Discussionsupporting
confidence: 56%
“…Alternatively, obesity itself might be the primary stimulus for either global overactivation of the HPA axis resulting in increased circulating cortisol concentrations, or increases in cortisol availability or activity at the level of the target tissues, or both. Chronically increased glucocorticoid production and increased hair cortisol (consistent with chronic free cortisol excess) have been associated with obesity in several studies in people,38, 39, 40, 41 and are consistent with long‐standing over‐activity of the HPA axis in obese states. Tissue cortisol metabolism also appears to be altered in obesity.…”
Section: Discussionmentioning
confidence: 61%
“…Urinary cortisol has been reported increased in obese individuals compared to lean individuals, but this increase is generally not reflected in serum or salivary cortisol levels (24). We found that in both adult and pediatric obese patients, HCC are increased compared to non-obese healthy controls (29,30). Furthermore, HCC positively correlates with BMI in multiple other studies (21,28,31,32,33,34).…”
Section: Cardiometabolic Statusmentioning
confidence: 51%